Women's Writing from the Low Countries 1200-1875 : a Bilingual Anthology. - Van Gemert, Lia (Amsterdam anthologies., 2010)
This landmark bilingual Dutch-English anthology introduces women's writing in the Low Countries from 1200 to 1875 through a variety of texts characterised by the religious, social, political and feminist engagement of their authors, as well as their extraordinary artistic achievement. Dutch and Flemish female writers produced work of ardent religious passion, ranging from medieval mysticism through the scathing anti-Reformation polemic to pious Anabaptist reflections. Other writers addressed current social and political debates or demonstrated fierce feminist engagement. Talented authors made.